Modern Argentine Poetry - Bollig, Ben (Iberian and Latin American studies., 2011)
This book explores the themes of displacement, exile and migration in the work of the most important Argentine poets since the 1950s. The book outlines the poetry of key authors in the second half of the twentieth century as well as writing by younger poets at the turn of the century. It includes generous selections of the original poems with new translations into English by the author.